Socialization of Lactation Massage to Postpartum Mother - Dwiyanti, Ni Kadek Neza; Rahayuni, Ni Wayan Sri (Jurnal Abdimas ITEKES, 2021)
Indonesia's health profile in 2016 shows that the coverage of infants who are breastfed for up to six months is only 29.5%. This figure is still far from the national target of 80%. Based on data from the profile of the Bali Provincial Health Office, the coverage rate of exclusive breastfeeding in Bali is 72.8%. By district or city, exclusive breastfeeding coverage in Badung Regency is 70.29%, Buleleng 61.95%, Gianyar is 80.02%, Jembrana is 84.7%, Karangasem is 69.68%. From these data, it can be seen that Gianyar Regency and Jembrana Regency have succeeded in achieving the national target (Bali Provincial Health Office, 2016). Meanwhile, the percentage of babies who received exclusive breastfeeding specifically at the age of 0 to 6 months in Bali Province was 30.1% (Kemenkes, 2016) The role of midwives in carrying out their profession must be in accordance with the existing midwifery concept in accordance with the results of the 2011 IBI National Work Meeting. One of the roles of the midwife during the postpartum period is to make home visits at least 3 times to monitor the condition of the mother and baby after giving birth and ensure that the baby is exclusively breastfed. In addition to home visits, the role of the midwife is also to provide counseling, counseling and socialization regarding proper breast care through lactation massage (Maternal and Child Health, 2016). The target of the program that will be carried out is to improve the health of mothers and babies by providing socialization about lactation massage to facilitate milk production. The output of the resulting program is an increase in the health status of mothers and babies.